Tổng hợp và nghiên cứu hình thái, cấu trúc tính chất của màng Fe3O4 tạo thành trên nền thép bằng phương pháp oxi hóa hóa học - Mai Thanh, Đinh Thị; Lan, Ngô Thị; Tú, Doãn Anh (Vietnam Journal of Chemistry, 2015)
Iron oxide layers formed on mild steel substrates in alkaline media by chemical method were studied. The effects of some factors such as: NaOH, NaNO3, NaNO2 solution concentration, temperature on synthesized magnetite films on mild steel were investigated. Morphology and structure of the oxide film on mild steel, were formed in solution of (500 g/L NaOH, 100 g/L NaNO3, 200 g/LNaNO2), at temperature 120 oC, in 40 minutes were studied. The results showed that synthesized magnetite films have thickness 1.29±0.20 mm, crystal uniform globes, average diameter 20 nm.